2005
DOI: 10.3200/jmbr.37.6.425-436
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Motor Control: Movement Attributes Following Affective Picture Processing

Abstract: The authors investigated the impact of emotion on the performance of a square-tracing task after participants (N = 40) were exposed to pleasant (P), unpleasant (U), and neutral (N) pictures. Physiological and self-report measures indexed affective valence and arousal. In Experiment 1, greater error followed exposure to 4 consecutive U images than exposure to 4 consecutive P images. Speed of performance did not vary as a function of valence. In Experiment 2, participants viewed 1 slide per trial within a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 26 publications
6
79
1
2
Order By: Relevance
“…However, the reliability of self-report and physiological responses to the images used in the current study has been consistenyly demonstrated (Bradley, Codispoti, Cuthbert, & Lang, 2001). Also, there is no evidence that pairing emotion and motor processes alters the typical pattern of emotional reactivity demonstrated when passively viewing emotional images (Coombes, Janelle, & Duley, 2005;Schmidt et at., 2009). Future research efforts are needed to (a) qualify these findings in healthy and clinical samples across the lifespan (Christou et al, 2004), (b) investigate the cortical and subcortical neural circuits that underlie the interaction between emotion and movement (Borsook, 2007;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;Pessiglione et al, 2007;Schmidt et al, 2009;van Loon et al, 2010), and (c) examine the implications of emotion-induced changes in movement in a variety of performance settings (Woodman et al, 2009).…”
Section: Discussionmentioning
confidence: 62%
“…However, the reliability of self-report and physiological responses to the images used in the current study has been consistenyly demonstrated (Bradley, Codispoti, Cuthbert, & Lang, 2001). Also, there is no evidence that pairing emotion and motor processes alters the typical pattern of emotional reactivity demonstrated when passively viewing emotional images (Coombes, Janelle, & Duley, 2005;Schmidt et at., 2009). Future research efforts are needed to (a) qualify these findings in healthy and clinical samples across the lifespan (Christou et al, 2004), (b) investigate the cortical and subcortical neural circuits that underlie the interaction between emotion and movement (Borsook, 2007;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;Pessiglione et al, 2007;Schmidt et al, 2009;van Loon et al, 2010), and (c) examine the implications of emotion-induced changes in movement in a variety of performance settings (Woodman et al, 2009).…”
Section: Discussionmentioning
confidence: 62%
“…From an affective perspective, it has been demonstrated that pleasant and unpleasant emotional cues have a differential impact on subsequent performance accuracy (Coombes, Janelle, & Duley, 2005). Specifically, Coombes et al, (2005) demonstrated an increase/decrease in accuracy during a tracing task following the presentation of relative affective stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings provide further evidence that an emotionally driven arousal response impacts the motor system, and this integration is reflected in emotion-driven changes in CST excitability. However, despite a growing database that addresses the influence of emotion on motor function at the behavioral and neurophysiological level (e.g., Coombes et al, 2006Coombes et al, , 2007aCoombes et al, , 2007bCoombes, Gamble, Cauraugh, & Janelle, 2008;Coombes et al, 2005;Oathes et al, 2008;Oathes & Ray, 2006) and a well-established body of literature that has focused on the neural correlates of emotional valence and emotional arousal (e.g., Grimm et al, 2006;Sabatinelli et al, 2005), our understanding of the mechanism(s) that integrate emotional and motor processes in the human brain remains vague.…”
Section: Force Productionmentioning
confidence: 99%
“…To assimilate previous TMS findings that have shown an arousal effect on CST excitability (Baumgartner et al, 2007;Hajcak et al, 2007) and behavioral findings that have shown a valence effect on motor output (Chen & Bargh, 1999;Coombes et al, 2006Coombes et al, , 2007aCoombes et al, , 2007bCoombes, Janelle, & Duley, 2005;Rotteveel & Phaf, 2004), in the present study, we examined how viewing emotional images while engaging the motor system via the preparation of a ballistic extension movement would modulate CST excitability. Pursuant to this aim and to replicate a previously used behavioral protocol (Coombes et al, 2007a(Coombes et al, , 2007b, we held the direction of the required movement constant (i.e., extension) and manipulated emotional state through the presentation of pleasant, unpleasant, and neutral images.…”
mentioning
confidence: 93%